Getting to the heart of hERG K+ channel gating. (15th June 2015) - Perry, Matthew D.; Ng, Chai‐Ann; Mann, Stefan A.; Sadrieh, Arash; Imtiaz, Mohammad; Hill, Adam P.; Vandenberg, Jamie I.
Abstract : Abstract: Potassium ion channels encoded by the human ether‐a‐go‐go related gene (hERG) form the ion‐conducting subunit of the rapid delayed rectifier potassium current ( I Kr ). Although hERG channels exhibit a widespread tissue distribution they play a particularly important role in the heart. There has been considerable interest in hERG K + channels for three main reasons. First, they have very unusual gating kinetics, most notably rapid and voltage‐dependent inactivation coupled to slow deactivation, which has led to the suggestion that they may play a specific role in the suppression of arrhythmias. Second, mutations in hERG are the cause of 30–40% of cases of congenital long QT syndrome (LQTS), the commonest inherited primary arrhythmia syndrome. Third, hERG is the molecular target for the vast majority of drugs that cause drug‐induced LQTS, the commonest cause of drug‐induced arrhythmias and cardiac death. Drug‐induced LQTS has now been reported for a large range of both cardiac and non‐cardiac drugs, in which this side effect is entirely undesired. In recent years there have been comprehensive reviews published on hERG K + channels (Vandenberg et al . 2012) and we will not re‐cover this ground. Rather, we focus on more recent work on the structural basis and dynamics of hERG gating with an emphasis on how the latest developments may facilitate translational research in the area of stratifying risk of arrhythmias.